2023
DOI: 10.1002/adsr.202200073
|View full text |Cite|
|
Sign up to set email alerts
|

Printed Electronics Technologies for Additive Manufacturing of Hybrid Electronic Sensor Systems

Abstract: Requirements for the miniaturization of electronics are constantly increasing as more and more functions are aimed to be integrated into a single device. At the same time, there are strong demands for low-cost manufacturing, environmental compatibility, rapid prototyping, and small-scale productions due to fierce competition, policies, rapid technical progress, and short innovation times. Altogether, those challenges cannot be sufficiently addressed by simply using either printed or silicon electronics. Instea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 236 publications
(406 reference statements)
0
6
0
Order By: Relevance
“…The synergies from combining 2D printing technologies and hybrid electronics with novel composite materials for advanced capabilities and new areas of application are very promising for progress in nanoelectronics. 20 In the present study, an ultrahigh current response (up to 4 orders of magnitude) was demonstrated for composites (graphene with PEDOT:PSS or G:h-BN:PEDOT:PSS) printed on a paper substrate. The ultrahigh sensitivity, S, was found to be ((2.0-3.3) Â 10 6 )% for both composite thin layers (GPP and GBNPP, 2-3 printed layers) for a relative humidity (RH) range of 20-80%.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…The synergies from combining 2D printing technologies and hybrid electronics with novel composite materials for advanced capabilities and new areas of application are very promising for progress in nanoelectronics. 20 In the present study, an ultrahigh current response (up to 4 orders of magnitude) was demonstrated for composites (graphene with PEDOT:PSS or G:h-BN:PEDOT:PSS) printed on a paper substrate. The ultrahigh sensitivity, S, was found to be ((2.0-3.3) Â 10 6 )% for both composite thin layers (GPP and GBNPP, 2-3 printed layers) for a relative humidity (RH) range of 20-80%.…”
Section: Introductionmentioning
confidence: 56%
“…The synergies from combining 2D printing technologies and hybrid electronics with novel composite materials for advanced capabilities and new areas of application are very promising for progress in nanoelectronics. 20…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of plasma enabled PECVD technology to meet the process requirements for the thin-film encapsulation of OLEDs, and its related encapsulation process link is practical to this day. In 2008, Kateeva, founded by C. Madigan et al of MIT, proposed inkjet printing (IJP) technology [47]. The growth of thin-film materials is achieved by directly spraying an ink containing the corresponding nano-composition on a flexible or rigid substrate [48,49].…”
Section: Thin-film Packaging Technology and Its Flexible Applicationsmentioning
confidence: 99%
“…Printed layers First, the contact of ink and stencil with the substrate should be considered, which results in contact or non-contact printing, which must be distinguished. Contact printing techniques include [2,3] gravure printing, offset printing, flexographic printing, roll-to-roll (R2R) printing, and screen printing. The most common non-contact printing techniques include inkjet printing and aerosol-jet printing.…”
Section: Introductionmentioning
confidence: 99%